Analisis Kemampuan Representasi Matematis Siswa Kelas XI MIPA dalam Menyelesaikan Masalah Matematis di SMAN 1 Setu Bekasi - Putri, Rila Septia Pratama; Munandar, Dadang Rahman; Zulkamen, Rafiq (Universitas Dr. Soetomo, 2021)
The ability of students' mathematical representations in solving mathematical problems is not optimal and students are often mistaken in representing them, causing the problem solving solutions to be less precise. This study aims to analyze the mathematical representation ability of class XI high school students in solving mathematical problems. Phenomenology is used in this study, with research instruments in the form of tests and non-tests. Mathematical problems are given to the research subject, then the results of the answers are analyzed based on the mathematical representation used in solving the problem. Six students of class XI MIPA were selected as research subjects. The phenomenological data analysis techniques used consisted of epoche, horizontalization, cluster of meaning, and essence description. The results showed the mathematical representation ability of class XI high school students in solving different mathematical problems. There are six types of mathematical representations that students use to solve mathematical problems, namely symbolic (Si), written text (Ts), visual and symbolic combinations (VsSi), visual and written text combinations (VsTs), symbolic combinations and written text (SiTs), and a combination of visual, symbolic, and written text (VsSiTs). The reason students use this type of representation is the students' habits and experiences in solving mathematical problems. Keywords: Mathematical Representation, Mathematical Problems, Visual, Symbolic, Written Text. Abstrak Kemampuan representasi matematis siswa dalam menyelesaikan masalah matematis belum optimal dan siswa masih sering keliru dalam merepresentasikannya sehingga menyebabkan solusi penyelesaian masalah kurang tepat. Penelitian ini bertujuan untuk menganalisis kemampuan representasi matematis siswa SMA kelas XI dalam menyelesaikan masalah matematis. Fenomenologis digunakan dalam penelitian ini, dengan instrumen penelitian berupa tes dan non tes. Masalah matematis diberikan kepada subjek penelitian, kemudian hasil jawaban dianalisis berdasarkan representasi matematis yang digunakan dalam menyelesaikan masalah. Enam orang siswa kelas XI MIPA dipilih sebagai subjek penelitian. Teknik analisis data fenomenologis yang digunakan terdiri atas epoche, horizontalisasi, cluster of meaning, dan essence description. Hasil penelitian menunjukkan kemampuan representasi matematis siswa SMA kelas XI dalam menyelesaikan masalah matematis berbeda-beda. Ada enam jenis representasi matematis yang digunakan siswa untuk menyelesaikan masalah matematis, yaitu simbolik (Si), teks tertulis (Ts), kombinasi visual dan simbolik (VsSi), kombinasi visual dan teks tertulis (VsTs), kombinasi simbolik dan teks tertulis (SiTs), dan kombinasi visual, simbolik, dan teks tertulis (VsSiTs). Penyebab siswa menggunakan jenis representasi tersebut adalah kebiasaan dan pengalaman siswa dalam menyelesaikan masalah matematis. Kata Kunci: Representasi Matematis, Masalah Matematis, Visual, Simbolik, Teks Tertulis.